HAKIKAT MANUSIA DAN IMPLIKASI DALAM ISLAM PERSPEKTIF IMAM AL- GHOZALI - Ahlul Fakih; Muhajir Muhajir; Umi Kultsum (IAIN Pontianak, 2023)
This study discusses human nature in an Islamic perspective according to Imam Al-Ghazali and the implications of this view in everyday life. The library research method is used in collecting data from various sources such as books, magazines, journals, and related literature available in the library. Google Scholar is the main source of information in collecting data. The collected data is analyzed and processed to produce conclusions. The results of this study are that according to Imam Al-Ghazali, humans consist of physical and spiritual aspects that are interrelated and influence one another. The implication of this view in everyday life is the importance of maintaining a healthy body through a healthy diet, exercise and adequate rest. In addition, avoiding behavior that damages the body and morals and strengthens faith and spirituality also helps to maintain a balance between the physical and spiritual aspects of human beings.